Imunodiagnóstico da neurocisticercose humana pelos testes Elisa e “western blotting” empregando diferentes preparações antigênicas de metacestódeos de taenia solium e de taenia crassiceps em amostras de líquidos cefalorraquidianos - Barcelos, Ivanildes Solange da Costa (1998)
Human neurocysticercosis is caused by Taenia solium metacestode infection in the Central Nervous System. The restriction for obtaining these larvas in the preparation of antigenic extracts used in the immunodiagnostic tests for human cysticercosis is a major problem for the standardization of new tests. The investigation of altemative homologous and heterologous antigens is necessary for the development of tests presenting liigh sensitivity and specifícity. The main goal of the present work was to carry out a comparative study of the total saline and sodium dodecyí sulfate (SDS) extracts of T. solium and Taenia crassiceps metacestodes. ELISA was initially used with total saline extract from T. solium metacestode, and afterward with three other antigen preparations. In addition, Westem-blotting was also studied for all antigenic extracts. It was studied 84 cerebrospinal fluid samples (LCR) by ELISA, 40 from patients with neurocysticercosis and 44 patients with other neurological alterations. Western- blotting was performed in 50 LCR samples, 40 from patients with neurocysticercosis and 10 from patients with other neurological diseases. The sensitivity of ELISA was 100%, 85%, 95% and 87.5% and the specifícity was 100%, 97.9%, 97.7% and 100%, respectively, for homologous total saline, heterologous total saline, homologous SDS and heterologous SDS extracts. Immunodominant peptides detected by Westem-blotting in decreasing percentage of recognition were: 64-68 and 45 kDa for homologous total saline; 108-114, 92-95, 64-68 and 88 kDa for heterologous total saline; 64-68, 108-114, 77 and 86 kDa for homologous SDS; and 108-114, 88 and 92-95 kDa for heterologous SDS antigenic preparation. Taken together, it can be concluded that all antigenic extracts can be used in the diagnosis of human neurocysticercosis, emphasizing that the SDS extracts presented higher protein concentrations than the saline extracts and therefore they provided better yield in the antigenic preparations.